AfricaRice weather: a free web-database - CGIAR Research Program on Rice (2021)
The website was released in 2017. we have data from 282 weather stations in 25 countries. Up to Oct, 2021, 2441 visits have been registered on the website. We uploaded data in AfricaRice dataverse (https://dataverse.harvard.edu/dataverse/Weather?q=&types=datasets&sort=dateSort&order=desc&page=1). Up to Oct, 2021, there have been 19499 downloads in total in AfricaRice dataverse.